1981
DOI: 10.1007/bf00365693
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of yeast mutants with thermoconditional sensitivity to the bifunctional alkylating agent nitrogen mustard

Abstract: Selection of mutants of Saccharomyces cerevisiae sensitive to the DNA cross-linking agent nitrogen mustard (HN2) at two temperatures (23 °C and 36 °C) yielded two isolates with thermoconditionally enhanced (ts) sensitivity to the mutagen. Both were due to single recessive nuclear genes. Mutant allele snm1-2 (ts) showed mainly ts-sensitivity to HN2, whereas mutant allele snm2-1 (ts) conferred ts-sensitivity to HN2, half mustard (HN1) and UV. In temperature-shift experiments it was determined that the functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Temperature-shift experiments show a complete Pso2p function within 5-6 h after introduction of ICL by HN2 treatment [28]. Pso2p has a nuclear localisation signal and indeed is localized there [29].…”
Section: Genes Pso1 Pso8 and Pso2 Encode Proteins Directly Involvedmentioning
confidence: 98%
See 1 more Smart Citation
“…Temperature-shift experiments show a complete Pso2p function within 5-6 h after introduction of ICL by HN2 treatment [28]. Pso2p has a nuclear localisation signal and indeed is localized there [29].…”
Section: Genes Pso1 Pso8 and Pso2 Encode Proteins Directly Involvedmentioning
confidence: 98%
“…Thermoconditional mutant snm1-2ts [28], now called pso2-12ts [7] carries two silent point and a missense mutation that replaces glycine with arginine at aa position 256 [29], thereby altering the hydrophilic domain of the protein. Temperature-shift experiments show a complete Pso2p function within 5-6 h after introduction of ICL by HN2 treatment [28].…”
Section: Genes Pso1 Pso8 and Pso2 Encode Proteins Directly Involvedmentioning
confidence: 99%
“…The importance of SNM1A in human ICL repair has only recently been appreciated ( 17 ), despite its yeast homologue (Pso2) having been shown to play an essential role in ICL repair ( 23 , 36 , 37 ). Prior studies demonstrating that SNM1A is able to rescue ICL repair defects in pso2 -deficient cells suggest that SNM1A and Pso2 share common activities required for ICL processing ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yeast mutants cells hypersensitive to ICL-inducing agents were identified in the early 1980s by two independent genetic screenings in Saccharomyces cerevisiae, which showed sensitivity to photoactivated psoralen (PSO2) [4] and sensitivity to nitrogen mustard (SNM1) [5]. It was later demonstrated that these genes are allelic [6] and the nomenclature PSO2 was adopted to unify them [1].…”
Section: Introductionmentioning
confidence: 99%